Disco polo (today) as an example of extended multimodality - Skowronek, Bogusław (Papers in Linguistics, 2023)
In the text, I discuss disco polo as a cultural phenomenon, a forum for building a semiotic and emotional community. This trend still functions in the form of various texts – music tracks, music videos and Internet comments. All of them are characterized by multimodality, treated as a combination of various semiotic strands (words, music, moving image). The interaction of these bands and their evocation of various meanings over several decades is what I call extended multimodality.